Self-oscillation and period adding from resonant tunnelling diode–laser diode circuit - Figueiredo, J. M. L. (2008)
A hybrid optoelectronic integrated circuit comprising a laser diode driven by a resonant tunnelling diode can output various optical and electrical signal patterns that include self-sustained oscillations, subharmonic and harmonic locking and unlocked signals, with potential applications in optical communication systems.